IN SILICO SCREENING AND BIOLOGICAL EVALUATION OF THE COMPOUNDS OF Justicia gendarussa LEAVES EXTRACT AS INTERFERON GAMMA INDUCER: A STUDY OF ANTI HUMAN IMMUNODEFICIENCY VIRUS (HIV) DEVELOPMENT - Sinansari, Restry; Prajogo, Bambang EW; Widiyanti, Prihartini (African Journal of Infectious Diseases (AJID), 2018)
Background: Justicia gendarussa Burm f. (Achanthaceae) has been known as traditional medicine in Indonesia. It contains of flavonoids and alkaloids. This study was conducted to evaluate the effect of J. gendarussa on the profile of IFN-γ on mice (Mus musculus). Molecular docking test was also conducted to determine the interaction of alkaloids and flavonoids on the J. gendarussa leaves against IFN-γ receptor. It is expected that this research will provide scientific information on the development of J. gendarussa leaves as an anti-HIV drug. Materials and Methods: The molecular docking test was performed by using Molegro Virtual Docker software to predict the interaction of alkaloid and flavonoid compounds of J. gendarussa leaves with IFN-γ receptor. In the in vivo test, the effects of 70% ethanol extract, fractionated 70% ethanol extract, and water extract of J. gendarussa leaves were evaluated on the profile of IFN-γ stimulation on mice (Mus musculus). The test was performed by administering the three gendarussa extracts into the nine groups of mice for 14 days. Results: Based on the molecular docking test, it was found that flavonoid of J. gendarussa leaves have lower effects on the IFN-γ receptor than the alkaloids. From the in vivo test on mice, it was found that the fractionated 70% ethanol extract of J. gendarussa leaves did not induce the level of IFN-γ. On the other hand, both 70% ethanol and water extract of J. gendarussa leaves induced the production of IFN-γ. Conclusion: Fractionated 70% ethanol extract of J. gendarussa does not induce the production of IFN-γ, so it can be developed as anti HIV drugs.